Comparisons of Chemical and Pesticide Usage between Burley and Rice Farming: Economics Cost should be Realized - Jaroensathapornkul, Jirawat (Naresuan University Journal: Science and Technology (NUJST); Vol 22 No 1 (2014): January-April 2014, 2014)
Since the year 2000, the Thai government has started to become aware of problems associated with chemical and pesticide residues left on tobacco, especially burley, which is grown in Sri Sumrong district, Sukhothai Province, the main region for burley farming in Thailand. This research attempted to compare and analyze the economics cost per hectare resulting from the chemicals and pesticides used in burley and rice farming in this area. The two sample groups in this study were 80 families who grew burley in Tub Peung subdistrict and 50 families who grew rice in Ban Rai subdistrict. The survey is carried out using a standard questionnaire with structured questions. The findings were that 58.75 % of burley farmers used highly hazardous chemicals and pesticides according to WHO standards. The statistically significant difference in the amount of chemicals used in burley farming and those used in rice farming was 0.05 (p = 0.05). Additionally, the economics costs resulting from chemical and pesticides use in burley farming were 2,307.44 baht (72.11, USD) per hectare. This cost was higher than those in rice farming, p=0.05. According to these findings, the province’s agriculture department should realize that increasing land productivity comes with not only higher income but also hidden economics costs from chemical usage. Keywords: Tobacco, Economics costs, Chemical and pesticide usage
Keywords: Tobacco, Economics costs, Chemical and pesticide usage